Assessment mangrove channel vulnerability of Langkawi using geospatial approaches / Nurfarihah Ibrahim - Ibrahim, Nurfarihah (2022)
Mangrove forests and their channels being one of the beneficial marine ecosystems on Earth that provides unique habitat and biodiversity opportunities. However, it has rapidly degraded in recent decades and many remaining habitats are suffering from unsustainable use. Mangroves are tropical species generally found on sheltered coastlines and estuaries. The main objective of this study is to assess the mangrove vulnerability index (MVI) of the Kilim’s River Langkawi Kedah, Malaysia. This MVI comprises five variables, i.e. river geomorphology, tidal range, mangrove species, DBH of mangrove and rate of sea level rise. The vulnerability levels are graded into five parts of vulnerability ranking for five managements unit of the mangrove channel vulnerability, which is very low, low, moderate, high and very high based on the rating values of the criteria. A thorough mangrove channel vulnerability index was derived by integrating the differential weighted rank values of the variables. The findings indicated that three parameter namely geomorphology, tidal range and mangrove species were categorized as high vulnerability level which is five. Meanwhile, DBH of mangrove and rate of sea level rise represent the low and high vulnerable category, respectively. In addition, the whole value of MVI is 50% which is moderate. Finally, the study’s conclusion included a systematic framework that researcher, decision-makers, and relevant authorities may utilize to create and implement mitigation and adaptation policies to address the implications of climate change on mangrove channel regions.